Carcinomas in the bladder with papillary and pseudopapillary morphology - not always urothelial - Daniel Abensur Athanazio; Maiara Ferreira de Souza; Maria Estela Pompeu do Amaral (BMC, 2020)
Abstract Background Urothelial carcinoma shows wide plasticity and broad morphologic spectrum. In many instances, the presence of papillary morphology is reassuring of the urothelial histogenesis of a high-grade invasive lesion but is not pathognomonic. Case presentation We reported herein four cases of carcinomas in the bladder with papillary morphology that had a final diagnosis different from urothelial carcinoma (3% of cases in a 42-month period). In high-grade tumors involving the urinary tract, the presence of papillary/pseudopapillary morphology is not sufficient to render a diagnosis of papillary urothelial carcinoma. Prostate adenocarcinoma, primary bladder adenocarcinoma or metastasis must be excluded in selected case scenarios.